Writing challenges and support for elementary students: facial emotions study - Nguyen Thi Xuan Yen; Nguyen-Bich-Thy Bui; Thien-Vu Giang (Institute of Advanced Engineering and Science, 2026)
Writing is one of the first basic skills that promote successful learning and mental health of elementary students. The 2018 Vietnamese curriculum reform has created challenges in the formation and practice of writing skills of lower elementary students. The primary research questions address: i) the key cognitive challenges in students’ writing performance; ii) the emotional experiences associated with writing tasks; and iii) the instructional strategies employed to enhance writing skills. Using a mixed-methods study design on 159 students and 12 teachers, through writing tests, facial action coding system (FACS) and semi-structured interviews, we recorded important insights. The findings showed that second-grade students demonstrated a higher significant advancement in writing. First-grade students mainly exhibit positive emotions with writing tasks. In contrast, second-grade students experience a higher prevalence of negative emotions. This shift suggests that as academic expectations increase, students have greater stress and emotional challenges, necessitating supportive interventions. This study’s findings can contribute to the national curriculum development, guide effective teaching practices, and contribute to wider discussions on educational reform within the Vietnamese context.